Injury rates of elite competitive weightlifters - Singh, G.; Kaur, B. (1999)
The goal of this study was to measure the occurrence and level of pain and incidence of 50 elite weightlifters (EWL) who participated in the 1998 Indian National Weightlifting Championships. The EWL had been training for 5.8 +/- 0.5 years (3 +/- 0.1 times per week; 94 +/- 6.1 minutes per workout). Participants were asked to respond to a questionnaire, previously validated by Brown and Kimball (1983), regarding the occurrence and level of pain in 14 regions of the body when lifting, immediately after a workout and between workouts. In addition, the number and severity of weightlifting related injuries that required medical intervention were assessed. During the previous year 50% of the EWL sustained a weightlifting-related injury. The majority of the injuries were due to muscle pull (47%) while the remainder were associated with tendonitis (28%), nerve damage (10%), skeletal insult (11%) and connective tissue damage (4%). The participants recorded that the lower back and shoulder regions had the highest occurrence and level of pain associated with weightlifting followed by the regions of the knees, the upper back, the neck and the elbows. Interestingly, 7% of the participants recorded that mild headaches occurred sometimes when they were weightlifting. In conclusion, elite weightlifting is associated with an elevated occurrence of lower back and shoulder musculoskeletal insult.